Psychometric Testing of the Premenstrual Symptoms Questionnaire and the Association Between Perceived Injustice and Premenstrual Symptoms: A Cross-Sectional Study Among Japanese High School Students - Takeda T; Yoshimi K; Yamada K (Dove Medical Press, 2020)
Takashi Takeda,1 Kana Yoshimi,1 Keiko Yamada2,3 1Division of Women’s Health, Research Institute of Traditional Asian Medicine, Kindai University, Osaka 589-8511, Japan; 2Department of Psychology, McGill University, Montreal, Quebec H3A 1G1, Canada; 3Department of Anesthesiology and Pain Management, Juntendo University Faculty of Medicine, Tokyo 113-0033, JapanCorrespondence: Takashi TakedaDivision of Women’s Health, Research Institute of Traditional Asian Medicine, Kindai University, 377-2 Ohno-Higashi, Osaka-Sayama, Osaka 589-8511, JapanTel + 81-72-366-0221 (Ext. 3393)Fax + 81-72-366-6661Email take@med.kindai.ac.jpPurpose: Premenstrual symptoms comprise a wide range of mood, behavioral, and physical symptoms occurring during the luteal phase. Perceived injustice is a belief linked to unfairness (ie, unnecessary suffering caused by illness). This study aimed to assess the validity and reliability of the Premenstrual Symptoms Questionnaire (PSQ), a patient-reported outcome measurement tool, and to examine the association between perceived injustice/perception of menstruation and premenstrual symptoms, as measured by the PSQ.Materials and Methods: Of 1388 female students, we analyzed 879 students with regular menstrual cycles who completed the PSQ, the premenstrual dysphoric disorder (PMDD) scale, the Somatic Symptom Scale-8 (SSS-8), and the Injustice Experience Questionnaire-chronic (IEQ-chr). First, the PSQ was examined for evidence of reliability and validity. Next, we used multiple regression and multivariate logistic regression to investigate the association between perceived injustice and premenstrual symptoms, using PSQ score as both a continuous variable and a dichotomous variable (premenstrual disorders or not). Moreover, the association between PSQ score and perceived menstruation was tested using student’s t-test and analysis of variance.Results: In terms of reliability, Cronbach’s α for PSQ score was 0.93. To assess structural validity, we used confirmatory factor analysis, which showed that the one-factor model and the two-factor model were a good fit. The PSQ showed good agreement with the PMDD scale. In terms of concurrent validity, PSQ total score correlated strongly with PMDD scale score, SSS-8 score, and IEQ-chr score (r = 0.88, 0.69, 0.57, respectively). IEQ-chr score predicted PSQ score (standardized regression coefficient = 0.53; P < 0.0001) and higher prevalence of premenstrual disorders (odds ratio: 1.15; 95% confidence interval: 1.12– 1.19). Negative perception of menstruation was associated with premenstrual symptoms.Conclusion: The PSQ showed sound psychometric properties among the adolescents in our sample. Perceived injustice and negative perception of menstruation were associated with premenstrual symptoms.Keywords: premenstrual syndrome, premenstrual disorders, injustice experience questionnaire-chronic, psychometric testing, validity